Uruf in Islamic Law Perspective - Tarmizi, Tarmizi (Journal of Islam and Science, 2020)
This paper discusses "Uruf in the perspective of Islamic law" by revealing problems, namely: (1) What is the position of uruf in istinbath of Islamic law, and (2) How is the application of uruf in Islamic Sharia laws. The position of uruf in istinbath of Islamic law is very important and can be a basis for legal considerations. The law of fiqhiyyah states that custom is punishable. Meanwhile, the application of uruf in Islamic Sharia laws is a source of law, especially in matters of muamalah, munakahah, and other social relations. Islamic law, which is closely related to interaction with fellow humans, is greatly influenced by the customs in society.